Rules of Vengeance - Reich, Christopher (New York Anchor Books, 2010)
When he is wrongfully implicated in a terrorist attack that interrupted his rendezvous with his dishonored spy wife, physician Jonathan Ransom tries to clear his name, but discovers that he may be a pawn in an international plot.
Keywords: a